Multi-instar descriptions of cave dwelling Erythraeidae (Trombidiformes: Parasitengona) employing an integrative approach - Dos Santos Costa, Samuel Geremias; Klompen, Hans; de Oliveira Bernardi, Leopoldo Ferreira; Gonçalves, Luciana Cardoso; Ribeiro, Dante Batista; Pepato, Almir Rogério (Zootaxa, 2019)
The life cycle of Parasitengona includes major morphological changes precluding an instar association based only on the morphology. This makes rearing and/or molecular data necessary to associate the heteromorphic instars. Most of the described species are known from either post larval instars or larva. Following a previous study on Palearctic Erythraeidae, in the present study the instar association was made through an integrative approach including rearing trials and molecular analysis of the cytochrome oxidase I (COI) gene with the Bayesian Generalized Mixed Yule Coalescent (bGMYC) algorithm for species delimitation. Two new cave dwelling Erythraeidae (Trombidiformes: Parasitengona) species are described Lasioerythraeus jessicae sp. nov. and Leptus sidorchukae sp. nov. including all active instars. Additionally, a complete description of the previously unknown adults of Charletonia rocciai Treat & Flechtmann, 1979 is provided with notes on the larva and deutonymph. We also demonstrate experimentally that Ch. rocciai larvae are not attached to the same individual host during the entire feeding stage. We discuss the presence of troglomorphisms in Le. sidorchukae sp. nov.; and the distribution of the species.